Preverjanje veljavnosti Vprašalnika o spanju, sedenju in telesni dejavnosti pri študentih - Šuc, Anja (Šport (Ljubljana), 2023)
Physical activity, sedentary behaviour, and sleep (i.e., 24-hour movement behaviours) have important impacts on students’ health and well-being. With the emergence of the 24-hour movement paradigm, there is a need for questionnaires that evaluate movement behaviours over the entire 24-hour cycle. The aim of this study was to test concurrent validity of the Daily Activity Behaviours Questionnaire (DABQ) among university students. Thirty-seven (25 females, 25 ± 2 years) students wore activity monitor (activPAL accelerometer) for seven days (24 hours per day) and completed the DABQ. The amount of sleep, sedentary behaviour, low intensity physical activity (LPA) and moderate-to-vigorous intensity physical activity (MVPA) captured by the DABQ and activPAL was calculated using proprietary software. The mean difference (DABQ - activPAL) between the two tools was 7 min/day for sleep (95% CI: -6, 20), -75 min/day for sedentary behaviour (95% CI: -128, -21), 105 min/day for LPA (95% CI: 53, 157) and -38 min/day for MVPA (95% CI: -51, -24). The Spearman correlation coefficient between DABQ and activPAL was 0.71 for sleep, 0.48 for sedentary behaviour, 0.59 for LPA and 0.50 for MVPA. The results of the study suggest adequate validity of the DABQ for the assessment of 24-hour movement behaviours in large epidemiological studies on university students.
Keywords: DABQ; gibalno vedenje; poraba časa; šport; študenti; študije; telesna aktivnost; vprašalniki